Empowering Adolescents against Breast Cancer - Syed Zulfiquar Ali Shah, Tarachand Devrajani, Anum Asif, Abshar, Shafaq Jabeen, Shagufta Laila Memon, Manahil Iftikhar, Aasfa Memon, (Pakistan Journal of Medical & Health Sciences, 2024)
One in nine Pakistani women may develop breast cancer at some point in their lives, making it the Asian country with the highest breast cancer incidence rate1. There were 34,066 newly diagnosed instances of breast cancer in Pakistani women in 2018, per data from the Cancer Research Group International2. The high mortality rate for breast cancer patients in the country is the result of a number of factors, including tardy referral to proper facilities and late diagnosis3. Different studies have concluded that early diagnosis is the key to curing cancer; if diagnosed early, patients have a greater likelihood of recovery and survival, and diagnosis at a later stage reduces the likelihood of survival, Therefore, it is crucial to stress the significance of early breast cancer detection and treatment4-6.